2020
DOI: 10.1109/tsp.2020.2975943
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Target Detection With an Arbitrary Spacing Distribution

Abstract: Motivated by the structure reconstruction problem in single-particle cryo-electron microscopy, we consider the multitarget detection model, where multiple copies of a target signal occur at unknown locations in a long measurement, further corrupted by additive Gaussian noise. At low noise levels, one can easily detect the signal occurrences and estimate the signal by averaging. However, in the presence of high noise, which is the focus of this paper, detection is impossible. Here, we propose two approaches-aut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…The estimation problem described in Section I-A is a simplified version of the cryo-EM reconstruction problem: the tomographic projection operator is omitted and we observe the same 2-D image multiple times with random in-plane rotations. This image recovery problem is an instance of the multi-target detection statistical model, in which a set of signals appear multiple times at unknown locations in a noisy measurement [3], [4], [13]. Here, we extend previous works by taking in-plane rotations into account, which forms an important step towards the analysis of the full cryo-EM problem.…”
Section: B Motivationmentioning
confidence: 84%
See 3 more Smart Citations
“…The estimation problem described in Section I-A is a simplified version of the cryo-EM reconstruction problem: the tomographic projection operator is omitted and we observe the same 2-D image multiple times with random in-plane rotations. This image recovery problem is an instance of the multi-target detection statistical model, in which a set of signals appear multiple times at unknown locations in a noisy measurement [3], [4], [13]. Here, we extend previous works by taking in-plane rotations into account, which forms an important step towards the analysis of the full cryo-EM problem.…”
Section: B Motivationmentioning
confidence: 84%
“…We have demonstrated the reconstruction of a target image from its noiseless invariants, and showed that our algorithmic approach is robust to noise. In future work, we intend to extend the framework to include the recovery of the target image from the observation M , to mitigate the separation condition [13], and to allow the recovery of multiple images simultaneously, in a similar fashion to [4], [6]. From a theoretical perspective, we wish to complement the empirical results of this work by proving that indeed a generic image f is determined uniquely by its rotationally-averaged third-order autocorrelation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, autocorrelation analysis provides a flexible framework to extend the multi-target detection model by relating the expected autocorrelations of the data with the signals, and all parameters necessary to describe the generative model. For instance, a follow-up paper relaxes the separation condition (1.2) and allows an arbitrary spacing of targets, as long as the signal occurrences do not overlap [29]. In that case, the autocorrelations of the data are functions of the signal and the unknown target distribution.…”
Section: Discussionmentioning
confidence: 99%